A justification of the social human rights - Seleme, Hugo Omar (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Beyond the debate on positive law referred to whether social rights have received international status of genuine rights, exists a philosophically debate that asks about their moral justification. Are there any human rights of moral nature –that may coincide or not with the recognized by positive law –whose contents are social or economic demands? Although the questions about the moral status and legal status are different, which is answered in the first case may have impact on how we think the international legal system should be designed. Arguing for the existence of moral rights with social content may be one reason–although not a definitive– to justify their fixing in positive rules. This article addresses only the problem philosophic ally, leaving aside the debate centered on the positive law. The objective is to offer the main guidelines of a moral justification of human rights. Such a justification not only allows giving information of some peculiar features of human rights, but it makes it possible to understand that the same moral reasons that underlie the civil and political rights apply to social rights. The matter has two parts. The first aims to develop the proposed justification. Once exposed the justification of human rights, the second part aims to show that it serves to sustain not only civil and political rights, but also social human rights.